Does the Firm Information Environment Influence Financing Decisions? A Test Using Disclosure Regulation - Albring, Susan; Banyi, Monica; Dhaliwal, Dan; Pereira, Raynolde (Management Science, 2016)
Extant theory claims a firm’s information environment impacts the choice between debt and equity financing. However, empirical evidence supporting this contention is limited. We evaluate this relation within the context of Regulation Fair Disclosure (Reg FD), which prohibited the use of selective disclosure. We find that firms with high proprietary costs of public disclosure are more likely to resort to debt financing following the passage of Reg FD. This relation is not sensitive to whether a firm has relied on selective disclosure in the pre-Reg FD regime. We also evaluate changes in firm disclosure policy and find that firms that adopted an expansive public disclosure policy are more likely to turn to equity financing. Overall, our evidence is consistent with the pecking order theory: firms with deteriorated firm information environments increase their use of less information-sensitive debt, whereas firms with improved information environments favor the use of equity financing. This paper was accepted by Mary Barth, accounting.